1961
DOI: 10.1002/art.1780040203
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the pathogenesis of ochronotic arthropathy

Abstract: TUDIES OF biochemical abnormalities in alcaptonuria during the course of S almost a century culminated recently in the demonstration that the basic defect is absence of homogentisic acid (HGA) oxidase in the tissues.l The mechanisms involved in the pathologic consequences of this biochemical defect have, however, been little studied or understood.The pathologic characteristics of the arthropathy that constitutes the principal lesion of ochronosis have been described in scattered instances.2 The anatomic findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

1962
1962
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 16 publications
(1 reference statement)
1
11
0
2
Order By: Relevance
“…Genetically, AKU is inherited as an AR trait (Virchow, 1866;Osler, 1904;Yules, 1957;O'Brien & Banfield, 1961). In our study, identical mutation in the homozygous state was identified in 11 of 16 nomads suffering from AKU.…”
Section: Discussionmentioning
confidence: 69%
“…Genetically, AKU is inherited as an AR trait (Virchow, 1866;Osler, 1904;Yules, 1957;O'Brien & Banfield, 1961). In our study, identical mutation in the homozygous state was identified in 11 of 16 nomads suffering from AKU.…”
Section: Discussionmentioning
confidence: 69%
“…The disease is not usually detected until adulthood because the only manifestation in childhood is darkening of urine. Arthritis tends to manifest in the third decade of life [1,5]. The most common serious effect of alkaptonuric ochronosis is the development of ochronotic arthropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The patient generally presents in the 3rd decade of life with degenerative arthritis and the diagnosis is suspected based on pigmentation of the ear cartilage and urine turning black on standing [1][2][3][4][5][6][7][8][9]. Ochronosis masquerading as pigmented villonodular synovitis is extremely rare.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent manifestations of the disease are diffuse calcification of the intervertebral disk followed by narrowing of the intervertebral space and specific type of arthropathy of the axial skeleton and the peripheral joints. Peripheral arthritis is observed in almost all patients, as they grow in age [15,16]. It first appears in knees, hips, shoulders, seldom in small joints of hands, and it is manifested by pain, limited morbidity and hydrarthrosis.…”
Section: Discussionmentioning
confidence: 99%